What Makes A Good Student: Voice from Teacher - Gesha Lailatul Fauziyyah; Raden Utari Maharani; Anggi Meilanti Rosdiani; Asep Suparman (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
Commonly, a good student equals good academic achievement. General people tend to associate good students with only excellence in academics. But in reality, another attribute will come up when people stated the definition of a good student. To make a clearer concept of a good student, finding another supporting attribute is needed. This present study aims to identify other attributes as a good student as perceive by the teacher. The teacher’s perspective is chosen because students first acquaint and the first observer is their teacher. Teachers’ perspectives such as teacher’s beliefs, opinions, and concerns are compiled as the source and obtained using interviews with semi- structured questions. Fifteen available teachers from different school levels and ages from 25 to 56 years old involved using convenience sampling in this study. The result of this study showed that teachers define a good student into four aspects or categories. The first is seeing from their academic skill, the second is dependent on the students’ personality, the third is their proficiencies and the last category is from the reflection. A surprising fact, teachers’ experiences, ages, and levels didn’t much influence their perspectives. Meanwhile, teachers’ gender affected their perspectives to define a good student.